Lymphocyte subsets for predicting inflammatory bowel disease progression and treatment response: a systematic review - Chen, Rirong; Li, Chao; Zheng, Jieqi; Fan, Zinan; Li, Li; Chen, Minhu; Chen, Baili; Zhang, Shenghong (Frontiers in Immunology, 2024)
Background: Lymphocytes play a key role in the pathogenesis of inflammatory bowel disease (IBD) and are widely explored as promising prognostic indicators. We aimed to outline the existing evidences on the capability of lymphocyte subpopulations to predict disease progression and treatment response in patients with IBD.The protocol for this review was registered in PROSPERO (registration ID: CRD 42022364126). Systematic retrieval was conducted using PubMed, Embase, and Web of Science databases. Original articles on the prognostic value of lymphocyte subsets in IBD published up to April 8, 2023 were eligible for inclusion. The Newcastle-Ottawa Scale was used to evaluate the risk of bias.Results: Twenty studies were ultimately included: eight evaluated the prediction of disease progression and 12 focused on the prediction of treatment response. According to the Newcastle-Ottawa Scale, three studies were of high quality, 16 were of moderate quality, and only one was of low quality. T-cell subpopulations, including CD4 + T cells, CD8 + T cells, and γδ T cells, are revealed to have prognostic capacity. Transmembrane tumor necrosis factor α-bearing lymphocytes, CD4 + T cells, CD8 + T cells, and Plasma cells are found to have the potential to predict the response to anti-TNFα agents. In contrast memory T cells, CD4 + T cells, and naï ve B cells may predict the response to vedolizumab.This systematic review identified several potential lymphocyte subset-related predictors. If verified in large cohort prospective studies, these findings could aid clinical decision-making.